The Process of Working Empty Mastering Students in Future Elementary School Teachers (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, the process of education and upbringing of elementary school students, increasing the activity of students with low mastery in the process of imparting knowledge given in textbooks, ensuring that they catch up with their peers, knowledge, Issues such as the formation of skills, qualifications and competences, the problems that arise in the acquisition of knowledge and the methods used to solve them, as well as the good results achieved through this, are revealed.